Socio-cognitive Skills in Children with Disruptive Behavior and Victims of Maltreatment - Ison-Zintilini, Mirta Susana; Instituto de Ciencias Humanas, Sociales y Ambientales (Pontificia Universidad Javeriana, 2009)
The goals were: 1) to compare cognitive skills in the solution of interpersonal problems in children with disruptive behaviour and those victims of maltreatment, and 2) to assess the emotions identified in both groups within frames of conflictive social interaction. The sample consisted of 49 boys / girls aged 6 to 10 years old – 27 children showing disruptive behaviour and the other 22 at risk for maltreatment. All of them live in Mendoza, Argentina. In both groups, cognitive skills in the solution of interpersonal problems were evaluated. We conclude that there are differences between the two groups – always taking age into consideration – in the following skills: identifying problem solving, generation of solution alternatives and anticipation of consequences. Moreover, those children victims of maltreatment clearly showed “fear” in a higher proportion than those with disruptive behaviour.